Buku Katalog Augmented Reality Sebagai Strategi Visual Branding Desa Wisata Lirikan Demping Kampung Tinthir - Alfin Ade Putra; Handriyotopo Handriyotopo; Bagong Pujiono; Catur Nugroho; Triana Dewi Kusumasari; Daru Almas Daffa; Sartika Sartika (Jayapangus Press, 2026)
This study aims to design an Augmented Reality (AR)-based catalog as a visual branding strategy for Dukuh Demping Tourism Village, Karanganyar. Despite its strong potential in ritual-based cultural tourism, Dukuh Demping has not yet been optimally developed due to the lack of integrated promotional media. In the post-pandemic context, there is a growing need for interactive and accessible digital-based promotion. This research adopts a practice-based research approach within visual communication design. Data were collected through participatory observation and in-depth interviews with key stakeholders, including the local tourism awareness group (Pokdarwis) and community members. The design process follows the Alberta Teachers reflective cycle (planning, action, observing, reflecting) and is integrated with visual branding principles by Marty Neumeier. The result of this study is an AR catalog titled Lirikan Demping, which integrates printed media with interactive digital content accessible via Instagram without requiring additional applications. The catalog features 3D visualizations, bilingual layout, and QR-based access to cultural performances, creating an experiential branding approach that enhances user engagement. Additionally, Grono Ireng videos also produced and posted in official YouTube channel of Tinthir Pokdarwis as branding strategy that carries virtual tourism messages. In conclusion, the integration of physical and digital media offers an effective and accessible visual branding strategy for tourism villages. However, the sustainability of AR technology remains a limitation, particularly due to dependency on third-party platforms. Future development should consider more sustainable alternatives such as WebAR.